PELANGGARAN PRINSIP IUS IN BELLO DAN IUS AD BELLO ATAS INVASI RUSIA TERHADAP UKRAINA - Muhammad Adam Firdaus (Ganesha Law Review, 2022)
In international relations, states need to exercise self-control or restraint and submit to international law. However, the Russian invasion of Ukraine stemmed from various problems between the two, causing various losses on a large scale. The invasion was not based on reasons legitimized by the United Nations and in Russia's invasion of Ukraine there were also allegations of attacks on civilian objects, namely the Ukrainian people themselves, which clearly included violations of international humanitarian law, so the invasion could not be justified.